2020
DOI: 10.1002/acn3.51214
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation of the endopiriform nucleus attenuates epilepsy in rats by network modulation

Abstract: Objective: Neuromodulatory anterior thalamic deep brain stimulation (DBS) is an effective therapy for intractable epilepsy, but few patients achieve complete seizure control with thalamic DBS. Other stimulation sites may be considered for anti-seizure DBS. We investigated bilateral low-frequency stimulation of the endopiriform nuclei (LFS-EPN) to control seizures induced by intracortically implanted cobalt wire in rats. Methods: Chronic epilepsy was induced by cobalt wire implantation in the motor cortex unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(115 reference statements)
0
6
0
3
Order By: Relevance
“…As inhibition in APC is particularly susceptible to kindling-induced long-term deficits 40 and that the APC is extensively connected with the “easiest ignition point”, endopiriform nucleus, this could be a main reason for the epileptogenicity of APC. Consistent with this notion, repeated, low-frequency stimulation (1 Hz) of the endopiriform nucleus suppresses the incidence of severe seizures 41 . It is also reported that low-frequency stimulation of APC can reduce seizures in the KA model 42 .…”
Section: Discussionmentioning
confidence: 75%
“…As inhibition in APC is particularly susceptible to kindling-induced long-term deficits 40 and that the APC is extensively connected with the “easiest ignition point”, endopiriform nucleus, this could be a main reason for the epileptogenicity of APC. Consistent with this notion, repeated, low-frequency stimulation (1 Hz) of the endopiriform nucleus suppresses the incidence of severe seizures 41 . It is also reported that low-frequency stimulation of APC can reduce seizures in the KA model 42 .…”
Section: Discussionmentioning
confidence: 75%
“…This consistency across models indicates that pulse modulation strategies can be applied to suppress or amplify neural activity in distinct brain circuits and conditions, whenever spontaneous and stimulation-evoked responses of comparable magnitude are generated in the targeted neuronal population. For example, underdamped neural responses in the hippocampus CA1 area evoked by stimulation of the endopiriform nucleus (23) could be employed, together with our pulse modulation strategies, to control hippocampal, frequency-specific neural activity.…”
Section: Discussionmentioning
confidence: 99%
“…A study in rodents demonstrated that miniscule injections of cholinergic agents to piriform cortex generated bilateral clonic seizures, an effect that was not replicated in other MTL structures 38 . Conversely, a recent study showed that electrical stimulation of the endopiriform nucleus improved seizure outcomes in mice 39 . In humans, a multicenter 2019 study of 107 adults demonstrated that removal of at least half of the piriform cortex in ATL increased the odds of seizure freedom by 16‐fold, and that these odds were directly proportional to the extent of piriform resection 16 .…”
Section: Discussionmentioning
confidence: 99%
“…38 Conversely, a recent study showed that electrical stimulation of the endopiriform nucleus improved seizure outcomes in mice. 39 In humans, a multicenter 2019 study of 107 adults demonstrated that removal of at least half of the piriform cortex in ATL increased the odds of seizure freedom by 16-fold, and that these odds were directly proportional to the extent of piriform resection. 16 These studies suggest that increased ablation of piriform cortex would also be associated with improved outcomes.…”
Section: Improved Coverage Of Piriform Cortexmentioning
confidence: 99%